Konsep Pendidikan Muhammadiyah - Dafri Harweli; Iswantir Iswantir (Departement of Mathematics Education, 2024)
This research aims to determine the concept of Muhammadiyah education. This research uses the library research method. The results of the research show that: (1) the background to the founding of Muhammadiyah is subjective factors, namely the verses of Al-and internal objective factors (the impurity of the practices of the Islamic ummah due to not making the Al-Qur'an and Sunnah the only major references for Muslims) and external objective factors (educational institutions owned by Muslims have not been able to prepare a generation that is ready to carry out the mission of Allah's caliphate on earth). (2) the aim of Muhammadiyah is